Exploring the right conduct of a manager: insights from Indian management. (1st January 2014) - Jain, Neetu
There has been an active interest in discovering 'Indianness' of Indian management and this can be attained by discovering the roots of our culture. Jaina wisdom and tradition as contributor to the field of Indian management are now being recognised and appreciated for their rich insights applicable to current competitive scenario. In Jaina ethics there is no conflict between man's duty to himself and to society. Here the highest good of society is the highest good of individual. One of the important treatises entitled 'Yoga-sastra' composed by Acharya Hemachandra presents a list of the 35 attributes of an ideal Sravaka or general principles of appropriate conduct. These rules of right or appropriate conduct have been prescribed for Shravakas, i.e., householders or laymen. These rules or principles are termed as Sravaka-gunas, i.e., qualities of an ideal householder. These rules are equally applicable to a manager in corporate context. This paper critically reviews the Marganusari Gunas from managerial perspective to extract nuances of conduct of a manager. The corporate of today can derive from this sutra valuable knowledge about the conduct of a manager or leader. The purpose of this paper is to explore the applicability of Marganusari Gunas in corporate context.